Upaya Peningkatan Pengetahuan melalui Edukasi Penatalaksanaan Emergency pada Kejang Demam di Wilayah Kerja Puskesmas Tanjung Sari - Nida Nafisah; M. Arifki Zainaro; Usastiawaty Cik Ayu Saadiah Isnainy; Setiawati (Jurnal Kesehatan Panca Bhakti Lampung, 2026)
Febrile seizures are a serious problem in children aged 6 months to 5 years and can be dangerous if not handled properly, for example causing poisoning. When parents do not know the correct treatment steps, they often take the wrong action and disappoint their child's condition. Health education for parents is needed to improve understanding of the management of febrile seizures. This study assessed whether educational interventions improved parental knowledge about emergency management of febrile seizures in the Tanjung Sari Community Health Center area. This quantitative study used a quasi-experimental pretest-posttest single-group design. The sample consisted of 30 mothers with children aged 0–5 years selected through accidental sampling. Before receiving education in the form of videos and coercion, the average parental knowledge score was 14.30 (SD = 3.602). After education, the score increased to 17.23 (SD = 2.063). This difference was statistically significant (p = 0.001 <? = 0.05). In conclusion, education effectively improved parental knowledge about febrile seizures and their management procedures.